Is more chocolate bad for poverty? An evaluation of cocoa pricing for Ghana’s industrialization and poverty reduction - Mulangu, Francis; Miranda, Mario; Maiga, Eugenie (International Food Policy Research Institute, 2015)
The purpose of this study is to understand how cocoa pricing options affect local processors’ cocoa acquisition, processing, and inventory decisions, with the ultimate goal of determining which policies best meet the multiple, but possibly conflicting, public policy objectives of maximizing government revenue, maximizing and stabilizing processor profits and throughput, and reducing poverty rates among cocoa beans producers. To evaluate these effects, we construct and numerically solve a structural dynamic model of a representative cocoa processor that maximizes the present value of current and expected future profits, given prevailing market conditions and cocoa pricing options. We then take the predicted cocoa pricing options to determine their associated poverty impacts among cocoa producers. We used this model to evaluate the appropriate cocoa pricing regime for attaining Ghana’s objectives of increasing cocoa processing capacity to 40% of total cocoa produced in Ghana. We found, for example, that an appropriate 35% discount on main-crop beans will increase processor revenue by 57%, while either reducing government revenue by 36% or reducing cocoa farmers’ income by a maximum of 22%, depending on who bears the burden of the discount.